NEWS MEDIA TEXT ANALYSIS REGARDING PERSONAL DATA LEAKAGE ON THE MAIN PAGE OF HARIAN KOMPAS - Purnama, Ade; Mayasari, Diyah; Abdullah, Yahya (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
This study attempts to determine how personal data leaks are covered in Harian Kompas in order to help readers comprehend the significance of the government's role in addressing such leaks by offering logical justifications from different perspectives. This study uses a qualitative methodology with a media text analysis approach using agenda setting theory, framing and priming theory. The primary data used in this study is a collection of news articles related to data leaks in the Harian Kompas, namely 5 news on the front page that appeared on September 12 to 16 2022 using documentation techniques as a data collection method. According to the findings of the analysis, Harian Kompas coverage of personal data leaks can be concluded if the reporting carried out by Harian Kompas in the context of personal data leaks is an agenda setting that is made and arranged in such a way with continuous publication on successive dates and times, and the discussion of this data leak focuses or frames on the role of government. This aims to criticize the government for being negligent and deemed to have failed in protecting the rights and data of its citizens which had been leaked many times, culminating in the case of leaking personal data of 1,3 billion sim card registration data, which until then had not been taken concretely by the government.